Identification and characterization of high‐yielding, short‐duration rice genotypes for tropical Asia - Won, Phyo L. P.; Liu, Hongyan; Banayo, Niño P. M.; Nie, Lixiao; Peng, Shaobing; Islam, Mohammad R.; Sta. Cruz, Pompe; Collard, Bertrand C. Y.; Kato, Yoichiro (Wiley, 2020)
Previous efforts to increase the yield of tropical rice (Oryza sativa L.) have focused on medium‐duration varieties. However, there is increasing demand for high‐yielding short‐duration varieties that can adapt to intensified cropping systems and climate change. Our goal was to identify physiological traits associated with high yield in elite short‐duration genotypes suitable for tropical Asia. We conducted field experiments in five consecutive growing seasons at the International Rice Research Institute, the Philippines. We selected genotypes in the first two seasons, then performed a detailed characterization of the most promising genotypes in the following three seasons. Of the 50 advanced‐generation genotypes, three had consistently high yield and early maturity, with yields 11 to 38% higher than that of ‘IRRI104’ (‘IR50404‐57‐2‐2‐3’), a short‐duration variety that is widely grown in Southeast Asia. These genotypes were 20 to 32 cm taller than IRRI104. We found that for grain growth, low source capacity, defined as stem nonstructural carbohydrates at heading plus biomass accumulation after heading, was the major factor for the low yield of IRRI104. Although sink capacity (spikelets m−2 × grain weight) in the promising genotypes was comparable to that of IRRI104, they had a 25 to 53% higher source–sink ratio (source capacity/sink capacity) than IRRI104, which was attributed to larger leaf area and greater biomass accumulation during the grain‐filling stage. This result suggests that slight changes in plant development to promote height combined with increased leaf area around heading would improve the yield of short‐duration rice varieties in tropical Asia.